Pembinaan Anak Rentan Tindak Kriminal melalui Kube pada Anak Binaan PSMP Antasena Magelang - Soviati, Bella Mulia; Fakhruddin, Fakhruddin; Ilyas, Ilyas (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2017)
This study aims to determine the process of planning and implementation of child counseling vulnerable to criminal acts through productive economic efforts in the assisted children PSMP Antasena Magelang and inhibiting factors of activity. The study used a qualitative approach. Research subjects consisted of 3 participants and 3 coaches, while the informant was activity manager and social worker. Data collection with observation, interviews, and documentation. The validity of the data using source and method triangulation. Data analysis techniques with data collection, data reduction, data presentation, and conclusions. The results show that planning by determining activities, targets, and budget funds tailored to the needs. Implementation in the form of giving of guidance material containing social guidance and productive economic effort. Coaching activities use 70% practice methods, the rest of lectures and discussions. Media coaching tailored to the needs. Inhibiting factors are lack of interest of children, lack of enthusiasm of the community in activities, unpredictable weather as obstacles in the development of oyster mushrooms, as well as falling after-sale price of catfish cultivation so that the capital is reduced.